Optimalisasi Kinerja Layanan Melalui Kepemimpinan Pemberdayaan, Kepribadian Proaktif, Dan Mediasi Keterlibatan Kerja Karyawan Frontliner Perbankan - Suriansyah, Erwin; Sridadi, Ahmad Rizki; Putri, Chika Adien Aulya; Pranindy, Jihan Salsabilla Ardine; Hardianto, Alviana Ajeng (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Balikpapan, 2025)
This study aims to analyze the influence of empowering leadership and proactive personality on service performance among banking frontliner employees in Tanah Bumbu Regency, South Kalimantan, with work engagement as a mediating variable. A quantitative approach was employed using Structural Equation Modelling-Partial Least Square (SEM-PLS), with a total of 172 respondents selected through purposive sampling. The results indicate that proactive personality significantly influences service performance, both directly and through work engagement. Meanwhile, empowering leadership does not have a direct impact on service performance but exerts a significant influence through work engagement as a full mediator. The findings suggest that banks should focus on strengthening employees' proactive personality and ensuring that empowering leadership is effectively implemented to enhance work engagement. However, this study is limited by its sample, which only focuses on banking frontliner employees, making the findings less generalizable to other industries. Future research should expand the sample scope and consider additional moderating variables, such as organizational culture or perceived organizational support.